Efficacy of Washing and Postharvest Treatments on Shelf Life and Quality of Oyster Mushroom - Das, PK; Hassan, MK; Akhther, N (Progressive Agriculture, 2013)
An experiment was conducted to study the efficacy of washing (control and 5% hydrogen peroxide) and post harvest treatments (control, hot water treatment, wrapping with unperforated and perforated plastic bags, wrapping with brown paper bag and wrapping with aluminum foil) on shelf life and quality of oyster mushroom. Postharvest treatments caused significant effects to influence weight loss, dry matter and protein contents, disease incidence and shelf life of mushroom. At the 7th day of storage, the highest weight loss (98.08%) was recorded in the untreated mushrooms, whereas the lowest weight loss (33.62%) was observed in mushrooms wrapped in unperforated plastic bag. Protein content was observed to be higher (28.98%) in mushrooms wrapped with unperforated plastic bag followed by perforated plastic bag (25.00%) at the 5th day of storage. Protein content declined dramatically in mushrooms held atambient conditions. The lowest protein content (2.97%) was recorded in the untreated mushrooms at the 7th day of storage. Unwashed mushrooms held atambient temperature had the highest incidence of disease. The longest shelf lifeof 6 days was recorded in mushrooms wrapped in unperforated plastic bag,whereas the shortest shelf life (3 days) was found in the untreated mushrooms. DOI: http://dx.doi.org/10.3329/pa.v21i1-2.16745 Progress. Agric. 21(1 & 2): 21 - 29, 2010